Extreme weather events - Lusted, Marcia Amidon (New York, NY Greenhaven Publishing, LLC, 2018)
In the wake of every killer hurricane, devastating wild fire, severe drought, or once-in-a-century flooding event, it has become commonplace for scientists, politicians, and ordinary citizens to debate whether or not these severe weather events can be tied directly to climate change and global warming. The scientific consensus generally indicates that we are beginning to see upticks in extreme weather due to warming and the resulting shift in weather patterns. Certain politicians, business interests, and energy executives, however, forcefully reject such connections as unproven and speculative. Where does the truth lie? This anthology collects the strongest viewpoints from across the ideological spectrum and the globe and allows readers to evaluate the arguments and evidence for themselves before forming an educated opinion. Bibliography, Detailed Table of Contents, Further Information Section, Index, Maps, Primary Sources, Sidebars, Websites.
Chapter 1: Extreme weather around the world -- 1. The global links between extreme weather and climate change / Daniel Huber and Jay Gulledge -- 2. The Atlantic Ocean brings a wave of climate change / The United Nations Environment Programme -- #g 3. Climate change and global warming 101 / Anup Shah -- 4. Costal resliience is key for the US and the World / Erin A. Thead -- 5. In the US hurricanes are a harbinger of climate change / John McQuaid -- 6. Weird weather around the world is cause for alarm / Christine Ottery -- Chapter 2: The effects of extreme weather -- 1. Climate has an impact global health / US Environmental Protection Agency -- 2. Animal populations are affected by climate upheaval / Juan Lubroth -- 3. In Eastern Africa, climate change affects food security / International Federation of Red Cross and Red Cresent Societies -- 4. Extreme weather may lead to extreme hunger / Physicians for Social Responsibility -- Chapter 3: Extreme weather and global warming -- 1. Global warming is man-made, not myth / Donald R. Prothero -- 2. Is global warming really that bad? / Melissa Denchak -- 3. How much of the world is responsibile for global warming? / Anup Shah -- 4. In Southeast Asia, cutting greenhouse gases is vital to survival / Murray Hiebert -- 5. Whose fault is climate change? / Frank Thomas -- Chapter 4: Coping with extreme weather -- 1. How various countries are tracking climate change / NPR News Staff -- 2. Sustainable development can combat global disaster / Tom R. Burns and Nora Machado Des Johansson -- 3. Preventing further climate upheaval isn't just the government's domain / Bonizella Biagini and Alan Miller -- 4. Europe must adapt to climate change / European Environment Agency -- Periodical and internet sources bibliography -- For further discussion -- Organizations to contact -- Bibliography of books.
Includes bibliographical references (pages 238-239) and index.
14 - 17 years
105951
Keywords: Climatic changes -- Juvenile works; Global warming -- Juvenile works; Severe storms -- Juvenile works